2020
DOI: 10.1111/itor.12766
|View full text |Cite
|
Sign up to set email alerts
|

Trade credit insurance in a capital‐constrained supply chain

Abstract: We examine the role of trade credit insurance in a capital-constrained supply chain with one (or two) lossneutral retailer(s) and one loss-averse manufacturer. We model the interplay between these supply chain participants as a Stackelberg game and analyze their operating and financing decisions. In one capitalconstrained retailer case, we find that either the manufacturer's high loss aversion level or the retailer's low initial capital motivates the manufacturer to adopt insurance. Insurance drives more credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…They find that the retailer can use barter exchange as a means of managing excess inventory and thereby improving profit. As the management of inventory risk (i.e., liquidation of excess inventory) lies at the heart of supply chain management (Choi, 2017; Li et al., 2020), it is worthwhile to examine the implications of barter exchange in the supply chain contracting setting. In specific, how does barter exchange influence the optimal strategies of the manufacturer and retailer in a supply chain?…”
Section: Introductionmentioning
confidence: 99%
“…They find that the retailer can use barter exchange as a means of managing excess inventory and thereby improving profit. As the management of inventory risk (i.e., liquidation of excess inventory) lies at the heart of supply chain management (Choi, 2017; Li et al., 2020), it is worthwhile to examine the implications of barter exchange in the supply chain contracting setting. In specific, how does barter exchange influence the optimal strategies of the manufacturer and retailer in a supply chain?…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al (2020) showed pricing strategies for dual-channel supply chains under a trade-credit policy. Li et al (2020) studied trade-credit insurance in a capital constrained supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al. (2020) link insurance with trade credit financing in a capital‐constrained chain consisting of one retailer and one/two risk‐averse manufacturer(s). Qin et al.…”
Section: Literature Reviewmentioning
confidence: 99%